Pengaruh ROE, EPS dan PBV terhadap harga saham (subsektor perusahaan properti dan real estate tahun 2018-2019 per triwulan) - Pungkas Dika Saputra; Supawi Pawenang; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to determine the effect of return on equity (roe), earnings per share (EPS), and price to book value (PBV) on the stock prices of companies in the property and real estate subsector. Sampling using purposive sampling method, the sample used in this study were 18 property companies listed on the Indonesia Stock Exchange during the period 2018-2019 per quarter. This study uses multiple linear regression analysis with the tools used is the SPSS version 16 program. The results of hypothesis testing are the variables return on equity (roe), earnings per share (eps), and price to book value (pbv) simultaneously or simultaneously have an effect. To share prices in property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2018-2019 per quarter. Partially the earnings per share and price to book value variables have a significant positive effect, while the return on equity (roe) variable has a significant negative effect on the stock prices of property and real estate sub-sector companies listed on the IDX in 2018-2019 per quarter. Keywords: earnings per share, return on equity, price to book value, stock price